The immediate upstream region of the 5′-UTR from the AUG start codon has a pronounced effect on the translational efficiency in Arabidopsis thaliana. Issue 1 (30th September 2013) - Kim, Younghyun; Lee, Goeun; Jeon, Eunhyun; Sohn, Eun ju; Lee, Yongjik; Kang, Hyangju; Lee, Dong wook; Kim, Dae Heon; Hwang, Inhwan
Abstract: The nucleotide sequence around the translational initiation site is an important cis -acting element for post-transcriptional regulation. However, it has not been fully understood how the sequence context at the 5′-untranslated region (5′-UTR) affects the translational efficiency of individual mRNAs. In this study, we provide evidence that the 5′-UTRs of Arabidopsis genes showing a great difference in the nucleotide sequence vary greatly in translational efficiency with more than a 200-fold difference. Of the four types of nucleotides, the A residue was the most favourable nucleotide from positions −1 to −21 of the 5′-UTRs in Arabidopsis genes. In particular, the A residue in the 5′-UTR from positions −1 to −5 was required for a high-level translational efficiency. In contrast, the T residue in the 5′-UTR from positions −1 to −5 was the least favourable nucleotide in translational efficiency. Furthermore, the effect of the sequence context in the −1 to −21 region of the 5′-UTR was conserved in different plant species. Based on these observations, we propose that the sequence context immediately upstream of the AUG initiation codon plays a crucial role in determining the translational efficiency of plant genes.